Model P-IKADKA sebagai Solusi Mengembangkan Modul Ajar Apresiasi Dongeng di Sekolah Dasar - Anindya, Arini; Apriliya, Seni; Putri, Agnestasia Ramadhani (UNIB Press, 2024)
This research was motivated by the unavailability of teaching modules that lead to appreciation learning and not using a special learning model for fairy tale appreciation. The aim of this research is to analyze the need for a fairy tale appreciation teaching module for Indonesian language subjects in class IV elementary school. The approach used in this research is a qualitative approach with descriptive methods. This research was conducted in the period 26 February - 1 March 2024 in two public elementary schools in Tasikmalaya City with research subjects namely two class IV educators and teaching module documents. The data collection techniques used were observation, document study and interviews. The data analysis technique used is the data analysis technique using the Miles and Huberman model in three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the fairy tale appreciation learning process is still not implemented optimally in an appreciative manner, because educators still have not planned learning optimally. Educators still use teaching modules provided by the government, so the learning model used does not use a learning model specifically for learning literary appreciation. Thus, there is no teaching module available that leads to learning to appreciate fairy tales in it. The implication is that it is necessary to develop an Indonesian language teaching module with fairy tale appreciation material that leads to appreciation learning using a learning model that is appropriate to literary appreciation learning, namely the P-IKADKA model with the syntax of introduction, introduction, connection, appreciation, discussion, comprehension and affirmation.